Knowledge, Attitude and Practices Of Mothers Regarding Infant & Young Child Feeding Practices (Iycf) In a Tertiary Care Hospital - Ara, Effat; Samsad, Iffat Ara; Sultana, Afroza; Sarmin, Zannat Ul; Aziz, Afrin; Hasnat, Ferdousi (Journal of Dhaka Medical College, 2023)
Background: Young Child Feeding Practices (IYCF) includes breast feedind and complementary feeding. Proper feeding practices are essential for proper nutrition, growth, development and survival of infant and young children.Maternal knowledge and feeding attitude has been shown to be a stronger predictor of breast feeding initiation and complementary feeding practice. Objectives: To evaluate the knowledge, attitude and practices of mothers regarding infant and young child feeding. Material and Methods: This cross sectional study was done in Dhaka Medical College Hospital, Dhaka from June 2017 to November 2017.A total number of 218 mothers having children between 0-23 months were included.Modified Iowa Infant Feeding Attitude Scale (IIFAS) and 5 point Likert scale was applied to assess maternal attitude towards infant and young children feeding. The relationship between infant feeding knowledge, attitude and practices and socio-demographic variables was tested by using Chi-square test. Relationship among mothers knowledge, attitude and practices regarding IYCF was showed by Spearman’s correlation. Results: The study result showed that, 83.5% mothers had good knowledge about IYCF but only half of them had good practice. Almost everyone ( 99.1% ) agreed that breast milk is best for new born baby. Most of the mother (94%) knew that exclusive breast feeding should be given for six months but only half of them (51.1%) practiced EBF.Though 72.5 % mothers had positive attitude towards breast feeding but about two third (63.6%) of them gave formula milk within 6 completed months. About two third of mothers (60.2%) used bottle for feeding their child. Most of the mother (94%) had knowledge about complementary feeding but only 55.7% mother provide complementary feeding accurately with atleast four different types of food. This study showed that educational background has significant relationship with KAP of mothers regarding IYCF. Conclusion: The study concluded that, majority of the mothers had good knowledge and a positive attitude towards breastfeeding and complementary feeding but they did not practice this properly.There is a strong association between mother’s educational background and KAP (Knowledge, attitude & practice) regarding IYCF. J Dhaka Med Coll. 2021; 29(1): 43-51